THE INFLUENCE OF BRAND AWARENESS AND PERCEIVED RISK TOWARD CONSUMER PURCHASE INTENTION ON ONLINE STORE (CASE STUDY OF THE CUSTOMER AT FEB UNSRAT MANADO) - Petahiang, Ivana Livia (Sam Ratulangi University, 2015)
ABSTRACT The use of internet for online shopping has become phenomena in recent years. OLX is operates as a mediator marketplace for selling product easy and quickly. In this way, brand awareness and perceived risk are the important factors to purchase or buy a product. The study purpose is to find out the influence of brand awareness and perceived risk toward consumer purchase intention on online store (case study of the customer at FEB UNSRAT Manado) simultaneously and partially. 45 students of FEB UNSRAT were surveyed as respondents. The result indicated the significant influence of brand awareness and perceived risk toward consumer purchase intention simultaneously. The recommendation is to Internet-based companies such as olx online store need to pay attention and focus the company's marketing strategy effectively and efficiently. The company should focus on brand awareness and perceived risk to increase purchase intention on the company website. Keyword: Brand Awareness, Perceived Risk, Consumer Purchase Intention